Microbially-mediated supergene dissolution and oxidization of solid manganese carbonate in the Malkantu manganese ore deposit in West Kunlun, Northwest China - Zhao, Ling-Nan; Huang, Qin; Pi, Dao-Hui; Zhang, Yi; Ding, Da-Qing; Ahmet, Sasmaz (Elsevier, 2025)
Supergenic manganese (Mn) oxide ores with high Mn concentrations, which are oxidized from sedimentary Mn carbonate ores, represent critical Mn resources and primary targets for industrial exploitation. Previous studies have suggested that most supergene Mn oxides are formed under warm and humid climatic conditions. However, the contribution of microbes to the formation of supergene Mn oxide deposits may have been significantly underestimated. In particular, under arid and cold conditions, where chemical weathering rates are extremely low, microbial processes may dominate, leading to Mn mineral alteration. In this study, we conducted a comprehensive morphological and mineralogical analysis of supergene Mn oxides in the Malkantu Mn deposit using advanced analytical methodologies, including X-ray diffraction, micro-Raman spectroscopy, scanning electron microscopy, and transmission electron microscopy. Our results revealed a range of microbially induced structures, including tubular borings, biofilm-like coatings, hyphae-like filaments, and nano-spherulite aggregations. These features provide compelling evidence for biologically mediated dissolution of Mn carbonates and the subsequent precipitation of secondary Mn oxides. The Mn carbonates, initially formed during the Late Carboniferous, were subsequently buried beneath the Permian volcanic-sedimentary sequences. The Cenozoic tectonic uplift exposed the Mn-rich layers to surface conditions characterized by arid climates, intense solar radiation, and minimal vegetation cover. Despite the seemingly inhospitable environment, microbial activity persisted, thus significantly influencing the alteration of Mn-bearing minerals. Our findings suggest a novel model for supergene Mn enrichment dominated by microbial processes rather than solely by climatic factors, offering new insights into supergene Mn ore genesis in arid, cold, and high-altitude settings.
Keywords: Supergene manganese oxide; Microbial dissolution; Malkantu Mn deposit; Weathering of manganese carbonate; West Kunlun